Euthanasia and other end of life decisions and care provided in final three months of life: nationwide retrospective study in Belgium. (30th July 2009) - Van den Block, Lieve; Deschepper, Reginald; Bilsen, Johan; Bossuyt, Nathalie; Van Casteren, Viviane; Deliens, Luc
Abstract : Objective To explore the relation between the care provided in the final three months of life and the prevalence and types of end of life decisions in Belgium. Design Two year nationwide retrospective study, 2005-6 (SENTI-MELC study). Setting Data collection via the sentinel network of general practitioners, an epidemiological surveillance system representative of all general practitioners in Belgium. Subjects 1690 non-sudden deaths in practices of the sentinel general practitioners. Main outcome measures Non-sudden deaths of patients (aged >1 year) reported each week. Reported care provided in the final three months of life and the end of life decisions made. Multivariable regression analysis controlled for age, sex, cause, and place of death. Results Use of specialist multidisciplinary palliative care services was associated with intensified alleviation of symptoms (odds ratio 2.1, 95% confidence interval 1.6 to 2.6), continuous deep sedation forgoing food/fluid (2.9, 1.7 to 4.9), and the total of decisions explicitly intended to shorten life (1.5, 1.1 to 2.1) but not with euthanasia or physician assisted suicide in particular. To a large extent receiving spiritual care was associated with higher frequencies of euthanasia or physician assisted suicide than receiving little spiritual care (18.5, 2.0 to 172.7). Conclusions End of life decisions that shorten life, including euthanasia or physician assisted suicide, are not related to a lower use of palliative care in Belgium and often occur within the context of multidisciplinary care.